Assessing the compliance of special libraries towards Malaysian's 2010 special library guidelines / Nor Azrina Kassim - Kassim, Nor Azrina (Universiti Teknologi MARA, 2021)
The Perpustakaan Negara Malaysia (PNM) has published Special Libraries Guidelines 2010 (SLG 2010) to guide and reference special libraries in managing and adequately administrating the library. Providing special libraries with planning guides and evaluation measurements is the primary purpose of SLG 2010 development. Yet, no study was conducted to measure whether Special Libraries in Malaysia adhere to SLG 2010. Therefore, it is important to conduct a study to identify whether the special libraries in Malaysia comply with SLG 2010. This study attempts to assess the extent of compliance with SLG 2010 by two selected special libraries in Malaysia. The study examines libraries' compliance with SLG 2010 in four areas: budgets, human resources, services, and promotion. The interview, document analysis, and observation methods were used to gather data on the degree of compliance with SLG 2010 by the chosen special libraries. The investigation discovered that the two chosen special libraries are typically out of compliance with SLG 2010. The research revealed many factors contributing to SLG 2010 non-compliance, including a lack of knowledge about SLG 2010, top management decision-making, outdated guidelines, and guidelines authority. The findings of this research will assist the responsible authority in taking steps to raise the degree of SLG 2010 compliance among Malaysia's special libraries.